2003
DOI: 10.4049/jimmunol.170.1.597
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Accumulation and Function of Memory CD4 T Cells in Human IL-12 Receptor β1 Deficiency

Abstract: Defects in IL-12 production or IL-12 responsiveness result in a vulnerability to infection with non-viral intracellular organisms, but the immunological mechanisms responsible for this susceptibility remain poorly understood. We present an immunological analysis of a patient with disseminated Salmonella enteritidis and a homozygous splice acceptor mutation in the IL-12Rβ1-chain gene. This mutation resulted in the absence of IL-12Rβ1 protein on PBMC and an inability of T cells to specifically bind IL-12 or prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 53 publications
3
50
0
Order By: Relevance
“…2). These findings are in agreement with two earlier studies (25,26) in which the CCR7 low subset of memory CD4 ϩ T cells was observed to contain almost all IFN-␥-producing cells among CD4 ϩ T cells polyclonally activated using CD3 and CD28 mAbs. In one of these studies (26), the production of IL-4 by memory CD4 ϩ T cells was also largely restricted to the CCR7 low rather than the CCR7 high subset.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…2). These findings are in agreement with two earlier studies (25,26) in which the CCR7 low subset of memory CD4 ϩ T cells was observed to contain almost all IFN-␥-producing cells among CD4 ϩ T cells polyclonally activated using CD3 and CD28 mAbs. In one of these studies (26), the production of IL-4 by memory CD4 ϩ T cells was also largely restricted to the CCR7 low rather than the CCR7 high subset.…”
Section: Discussionsupporting
confidence: 83%
“…This modest reduction could reflect a general tendency of young children to produce fewer CCR7 low cells to antigenic stimuli, although this remains to be shown. Consistent with this idea is the recent finding that circulating monocytes from healthy infants and young children have a reduced capacity to produce IL-12 (36), a cytokine that is required for the accumulation of CCR7 low memory CD4 ϩ T cells with Th1 function (25). Although speculative, it is also plausible that the increased proportion of CCR7 low memory CD4 ϩ T cells in adults could reflect their greater cumulative exposure to natural infections that are effective at driving Th1 immune responses compared with the young children of our study, for whom a greater proportion of antigenic stimulation may be derived from vaccines that are relatively ineffective Th1 inducers.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations